Effectiveness of Indacaterol-Glycopyrronium in preventing COPD exacerbations in comparison to Salmeterol-Fluticasone (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
COPD exacerbations are complex events usually associated with increased airway inflammation, increased mucus production and marked gas trapping. These changes contribute to increased dyspnoea that is the key symptom of an exacerbation. Inhaled long acting bronchodilators not only control symptoms but also prevent exacerbations of chronic obstructive pulmonary disease (COPD). The purpose of the study was to compare the efficacy between Indacaterol-Glycopyrronium and salmeterol fluticasone (SFC) in preventing COPD exacerbations during 24 weeks of treatment. This randomised active-controlled trial was conducted at Department of Respiratory Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka involving 200 patients with COPD exacerbations. Patients were randomly divided into two groups; & treated with Indacaterol- Glycopyrronium 110/50 ug o.d. & Salmeterol-Fluticasone (50/500 ug b.i.d.) (SFC) respectively; & follow-up was done after 12 and 24 weeks. The FEV1 was significantly higher at 12 and 24 weeks in the Indacateol- Glycopyrronium group compared with SFC. Statistically significant improvements in peak FVC was observed in Indacaterol- Glycopyrronium when compared to SFC at week 12 and week 24. Our study result showed that Indacaterol-Glycopyrronium was superior to Salmeterol-Fluticasone in terms of prevention and optimal management of COPD exacerbation.BSMMU J 2021; 14(3): 43-49